Alkali metals decorated silicon clusters (SinMn, n = 6, 10; M = Li, Na) as potential hydrogen storage materials: A DFT study. (8th January 2022) - Jaiswal, Ankita; Sahoo, Rakesh K.; Ray, Shakti S.; Sahu, Sridhar
Abstract: In this article, we have studied hydrogen storage properties of alkali-metal decorated silicon clusters ( Si n M n, n = 6, 10; M = Li, Na ) using density functional theory (DFT). The electronic structure, stability and bonding properties of both bare and hydrogen adsorbed clusters are studied and verified using global reactivity descriptors and Quantum Theory Of Atoms in Molecules (QTAIM) study. No distortion in host clusters is observed upon adsorption. H2 bond lengths ( 0.74 Å – 0.75 Å ), H − AM bond distances ( 2.134 Å − 3.108 Å ) and adsorption energy (0.059eV − 0.141eV) confirmed the adsorption process to be molecular and physisorptive in nature. Li sites in Si6 Li6 and Si10 Li10 can bind up to 18H2 and 40H2 molecules respectively resulting in a maximum gravimetric density of 14.7 wt% and 18.7 wt% respectively. Similarly, Na sites in Si6 Na6 and Si10 Na10 can adsorb up to 18H2 and 40H2 molecules resulting in a maximum gravimetric density of 10.6 wt% and 13.6 wt% respectively. The gravimetric densities for respective clusters thus obtained are quite higher than the target 5.5 wt% as set by US-DoE. In addition to this, ADMP-MD simulation reveal that all the host clusters adsorb molecular hydrogen reversibly and can undergo room temperature (300 K) desorption. Graphical abstract: Image 1 Highlights: Alkali metal decorated Si clusters for hydrogen storage are computationally investigated. Adsorptions are molecular physisorption in nature (0.06 eV–0.14 eV). Maximum gravimetric density is achieved to be 18.7 wt%. ADMP simulation confirms reversible desorption at room temperature.